Penerapan Rukun dan Syarat Jual Beli dalam Transaksi Online Berdasarkan Ekonomi Syariah - Putri, Mutia Sari; Mardian, Husni; Susanto, Rindang (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
Buying and selling in Islam is not merely viewed from an economic perspective but also encompasses high moral and spiritual dimensions. In every transaction, whether in traditional markets, modern markets, or through digital platforms, values such as justice, honesty, and transparency must always be upheld. By conducting transactions in accordance with Sharia principles, individuals can gain benefits that are not only material but also receive blessings from Allah SWT. This study employs a library research method, aiming to examine and analyze relevant literature on the concept of buying and selling from an Islamic perspective. The primary sources used in this research include books of fiqh, publications on Islamic economics, and scholarly articles discussing various principles and regulations of trade according to Islamic law. The findings of this study indicate that buying and selling fall under muamalah, which is generally permissible unless there is evidence prohibiting it. After analyzing the essential elements and conditions of transactions in Islamic law, it can be concluded that online transactions do not contradict Islamic principles as long as they meet the necessary requirements regarding the contracting parties, the sighat (expressions of offer and acceptance), the transaction object, and the exchange value. However, the transaction must not involve any prohibited elements such as riba (usury), gharar (deception), harm, uncertainty, coercion, or infringement of others' rights. Additionally, the goods or services being traded must be halal and not contradict the teachings of the Quran and Hadith.